Psychometric Validation of the Digital Competence Questionnaire for Nurses - Christoph Golz PhD; Sabine Hahn PhD; Sandra M.G. Zwakhalen PhD (SAGE Open Nursing, 2024)
Introduction No brief questionnaire comprising knowledge, skills, and attitudes is available to measure digital competence among clinical practice nurses. Objective The aim was to evaluate the structural validity and internal consistency of the Digital Competence Questionnaire (DCQ) for Clinical Practice Nurses. Methods A cross-sectional study was conducted with English-speaking clinical practice nurses. Twenty-six items from an initial item pool, developed in a prior conducted Delphi Study, were included. Exploratory factor analysis for structural validity with “oblimin” rotation and a two-factor solution as well as internal consistency test using Cronbach's alpha were conducted. Results Data from 185 nurses was obtained. The final questionnaire comprised of 12 items allocated to two factors: knowledge & skills and attitude. Factor “attitude” explained 33% of the variance and factor “knowledge & skills” 24%, resulting in a cumulative explanation of the variance of 57% by both factors. Internal consistency per factor was satisfactory, with 0.81 and 0.91, respectively. Conclusion The DCQ for clinical practice nurses is valid and has satisfactory internal consistency. Researchers and nurse managers can use it to assess the level of digital competence among clinical practice nurses. Future psychometric validation of the DCQ for clinical practice nurses is required to allow a conclusion on the goodness of fit and reliability.